Influence of OH− Ion Concentration on the Surface Morphology of ZnO-SiO2 Nanostructure - Jessica Ven G. Tinio; Key T. Simfroso; Amber Dea Marie V. Peguit; Rolando T. Candidato (Journal of Nanotechnology)
The influence of varying OH− ion concentration on the surface morphology of chemically deposited ZnO-SiO2 nanostructures on glass substrate was investigated. The morphological features, phase structure, and infrared characteristics were examined by scanning electron microscopy (SEM), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR), respectively. Results revealed that silica significantly changes the hexagonal morphology of bare ZnO rod to “pointed tips” when using low initial OH− precursor concentration. Increasing OH− ion concentration resulted in a “flower-like” formation of ZnO-SiO2 and a remarkable change from “pointed tips” to “hemispherical tips” at the top surface of the rods. The surface capping of SiO2 to ZnO leads to the formation of these “hemispherical tips.” The infrared spectroscopic analysis showed the characteristics peaks of ZnO and SiO2 as well as the Si-O-Zn band which confirms the formation of ZnO-SiO2. Phase analysis manifested that the formed ZnO-SiO2 is of wurtzite structure. Furthermore, a possible growth mechanism is proposed based on the obtained results.